A study of the intention to use robo-advisory services in Malaysia - Chow, Chi Ving; Tan, Genevieve Xin Yii; Tan, Min Xin (2023)
In Malaysia, robo-advisory services have become increasingly popular in the financial industry. Hence, this study investigates the factors that determine the intention to use robo-advisory services in Malaysia. The proposed research model is based on the Unified Theory of Acceptance and Use of Technology Theory 2 (UTAUT2). More specifically, the independent variables included in the model are performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and trust. Furthermore, the target respondents for this study are individuals from the M40 income group in Malaysia. A total of 400 responses were collected and analysed through Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS software. The findings demonstrated that performance expectancy, social influence, hedonic motivation, price value, and trust are significant in affecting the behavioural intention to use robo-advisory services in Malaysia, except for effort expectancy and facilitating conditions, which showed an insignificant result. Moreover, this study would contribute to understanding the emergence of robo-advisory services in Malaysia and provide practical and theoretical implications for portfolio managers, robo-advisory firms, and researchers to aid in the future development of robo-advisory services and financial industry in Malaysia.